1993
DOI: 10.1002/jmv.1890390107
|View full text |Cite
|
Sign up to set email alerts
|

Detection of HTLV‐I and HTLV‐II infection in Africans using type‐specific envelope peptides

Abstract: Antibodies to HTLV were determined in 4,630 black African individuals from Zaire, Ghana and South Africa; 185 (4%) were confirmed as seropositive. Seroprevalance was 0.2% in a group of South African women, 0.9% among Ghanaian refugees in Belgium and from less than 1% to over 15% in various sites and populations in Zaire. With the use of HTLV-I and HTLV-II type-specific envelope peptides, 93% of confirmed HTLV seropositives were classified as HTLV-I. Five persons from the Haut Zaire region had HTLV-II serologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…HTLV-II infection in the African continent has also been reported (Delaporte et al, 1991;Goubau et al, 1992Goubau et al, , 1993aFroment et al, 1993;Gessain et al, 1994Gessain et al, , 1995Tuppin et al, 1996). (1995) have shown that two splice sites in the pX region of HTLV-IIa-Mo at positions 6807 and 6944 produced two additional dicistronic doubly spliced mRNAs, and they characterized the two proteins pl0 x~ and pll xv from the longest of these mRNAs.…”
Section: Introductionmentioning
confidence: 85%
“…HTLV-II infection in the African continent has also been reported (Delaporte et al, 1991;Goubau et al, 1992Goubau et al, , 1993aFroment et al, 1993;Gessain et al, 1994Gessain et al, , 1995Tuppin et al, 1996). (1995) have shown that two splice sites in the pX region of HTLV-IIa-Mo at positions 6807 and 6944 produced two additional dicistronic doubly spliced mRNAs, and they characterized the two proteins pl0 x~ and pll xv from the longest of these mRNAs.…”
Section: Introductionmentioning
confidence: 85%
“…HTLV-I sero-surveys in South Africa have focussed mainly on selected communities [15,[24][25][26][28][29][30], with little data from the general population. Caution must however be exercised when interpreting HTLV-I serological results on serum samples of African origin as unrecognized but related retroviruses may be present [26,30,44]. The relatively high HTLV-I seroprevalence rates reported in early studies [24,25,45] may therefore be overestimates as no WB confirmatory testing was done on sera found to be positive by enzyme immunoassay.…”
Section: Discussionmentioning
confidence: 99%
“…In this investigation no evidence of HTLV-I infection was detected in DBSs collected in 1993, while in 1994 a seroprevalence rate of 0-38 % (95 % confidence interval [CI] = 0-0l6-0160 %) was recorded in the same community, with an overall seroprevalence rate of 0-44% (95% CI=0 17-0-71%) for the region. In community-based studies, an HTLV-I seroprevalence rate of 02 % (95 % CI = 0-01-13 %) was reported in sera from 428 black South African pregnant women from the Pretoria area [44], and Maaga and coworkers [31] reported a seroprevalence rate of 0-2 % in sera collected in 1989 from 509 healthy black family volunteers from the Ga-Rankuwa area (north-west of Pretoria) of the Gauteng region. To date only one case of HTLV-II seropositivity has been recorded in South Africa, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The virus has been shown to be endemic in a number of native American Indian tribes (Biglione et al 1993;Black et al 1994;Ijichi et al 1993;Lairmore et al 1990; Levine et al 1993;Maloney et al 1992). HTLV-II infection in the African continent has also been reported (Delaporte et al 1991;Froment et al 1993;Gessain et al 1995;Goubau et al 1992Goubau et al , 1993aGoubau et al ,b, 1996Tuppin et al 1996).…”
Section: Introductionmentioning
confidence: 99%